Application of Reverse Vending Machines (RVMs): A Case Study in the UK - Peng, Zhiling (2016)
Traditionally, recycling service is provided by the government as the public service which includes kerbside collection, bring sites, household waste recycling centres and so forth. However, in today’s world facing increasing pressure from the environment, the engagement of business in recycling activities is desired. The development of technology has generated various modern recycling solutions. These new solutions allow the improvement in recycling effectiveness while enabling business to engage in the society’s recycling activities. One of these new recycling solutions is reverse vending machine (RVM). Stojanov (2015) defined this machine as ‘a device designed properly to identify and process empty beverage containers and to provide a means for a deposit refund on returnable containers’. Nowadays, there have been over 100,000 RVMs globally of which the most are in Europe and North America (RVC, 2014c; Sumitomo Corporation, 2008). Meanwhile, RVM has been widely considered as a simple, effective and cleaning recycling solution (Vending International, 2010). As one of the most influential countries in the world, the UK is currently facing challenges in improving its recycling performance. However, the UK still prefer traditional recycling solutions while new solutions such as RVMs remain relatively unpopular in this country. This paper will investigate the application of RVMs in the UK and try to explore the reasons of the machine’s limited employment in this country. In this paper, through case-based research, 28 UK RVM projects will firstly be presented aiming to provide a general understanding of RVMs’ application status in the UK. Next, the paper hypothesises that the reasons for RVM’s limited application derive from the impact of Deposit Refund System (DRS), awareness of RVM’s benefits, the impact of the public’s recycling attitudes and behaviours, the impact of the UK RVM projects’ operational practices, the impact of the UK’s recyclables market condition. Comparison with other countries where RVMs are more popular will be made. It is important to note that this paper does not attempt to reach a solid conclusion but to offer a starting point for future research.